The impact of globalization of the patent protection in the pharmaceutical industry tructure in developing countries - Meskin, Abdelhafid (Milev Journal of Research and Studies, 2017)
This present study aimed at analyzing the side effects of The Agreement of Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) in the area of pharmaceutical industry in the developing countries in general. It investigated the issue of whether the extension of such agreement ; would influence the attitudes of innovation in the pharmaceutical industry .It has been found that the effect of strengthening the protection of intellectual property in general, and pharmaceutical patent invention system in particular is associated with drugs, therapeutic categories, the behavior of the reference groups in the sector, and the consumer government without neglecting the pricing strategies of multinational companies.